Public-Private Partnerships : A Public Economics Perspective - Sadka, Efraim (IMF Working Papers; Working Paper ;, 2006)
Public-private partnerships (PPPs) involve the supply by the private sector of infrastructure and services deriving from infrastructure assets which have traditionally been supplied by the public sector. PPPs are spreading all over the world. It may be quite plausible that such arrangements were initially an attempt to evade expenditure controls and hide public budget deficits. But if they are properly designed and transparently reported, PPPs can enhance the efficiency of the provision of services that were formerly supplied solely by the public sector. This paper provides a public economics perspective on PPPs.